Characterizing regionalism in Asia: A modern global supply chain perspective - Shang-Jin Wei; Xinding Yu (Asian Development Bank (ADB), 2022)
This paper employs a modern global value chain (GVC) decomposition framework to quantify economic interdependence among Asian economies and between Asia and the rest of the world. It pays special attention to the value-added relationships among three sets of economies: those belonging to both Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and Regional Comprehensive Economic Partnership (RCEP), those belonging to one but not the other, and those belonging to neither. GVC linkages in value-added terms across economies are found to have grown faster than the value-added linkage through final goods trade. For GVC connections, indirect GVC linkages via third economies have been growing faster than the direct linkages. Finally, there is an increased tendency in Asia for both "near selling" of the value added in output and "near sourcing" of value added in inputs.
Keywords: F10; F15; F63; 330; global value chain; decomposition framework; economic regionalism; economic integration; value-added linkages